Contradictory Representations of the Child Figure in the Media: JonBenét Ramsey Murder Case Retellings on YouTube - Sylwia Gryciuk (European Journal of American Studies)
Even over 20 years after her death, JonBenét Ramsey remains the most recognizable child murder victim in recent American history, with her case being especially notorious for its sensational and elaborate media coverage. In this article, I take a look at an Internet community which—through the means of YouTube remixes—attempts to oppose the narratives popularized in the mainstream media, using the Ramsey case to offer counter-representations of the concepts of family, childhood, and girlhood. I also attempt to show that the outcome of this online activism does not correspond fully with the intent, as the videos in question often come close to complicity with the narratives which their authors try to subvert. This observation adds credence to the claim that cultural representations of children and childhood in contemporary English-language discourse at large feature a seemingly irreconcilable combination of sentimental innocence and disquieting eroticism.